2018
DOI: 10.17264/stmarieng.9.81
|View full text |Cite
|
Sign up to set email alerts
|

Asystole During Administration of Dexmedetomidine with Spinal Anesthesia: A Case Report

Abstract: Dexmedetomidine is a useful sedative drug that does not cause severe respiratory depression but sometimes causes hypotension or bradycardia. We encountered a case in which asystole occurred during transurethral lithotomy (TUL) that was performed under spinal anesthesia with administration of dexmedetomidine. The patient was a 73-year-old man whose medical history included radiation therapy for prostate cancer and TUL, which had been performed under spinal anesthesia without incident. Results of preoperative ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Tanskanen et al found that infusion of dexmedetomidine (0.4 µg/kg/h) causes the stability of heart rate and blood pressure compared to the placebo (16). Nevertheless, Amano et al reported that, dexmedetomidine administration might be associated with bradycardia, which may even lead to cardiac arrest (17).…”
Section: Discussionmentioning
confidence: 99%
“…Tanskanen et al found that infusion of dexmedetomidine (0.4 µg/kg/h) causes the stability of heart rate and blood pressure compared to the placebo (16). Nevertheless, Amano et al reported that, dexmedetomidine administration might be associated with bradycardia, which may even lead to cardiac arrest (17).…”
Section: Discussionmentioning
confidence: 99%